1978
DOI: 10.1007/bf01921930
|View full text |Cite
|
Sign up to set email alerts
|

Induction of developmental anomalies in mice by maternal stress

Abstract: The short-time restraint of pregnant mice on day 8 of gestation led to a significant increase of the anomaly rate in fetuses. This effect may be due to stress factors of endocrine origin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

1981
1981
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…In addition to standard tube, taping, and wire mesh restraints, confinement in an apparatus used to deliver radiation dosing to pregnant mice has been studied (Michel and Fritz‐Niggli, 1978). Following up on previous observations made during radiation experiments, the investigators used durations of 1.8, 10, 20, and 36 min on gd 8 and looked at abnormal fetuses (intrauterine growth retardation and external malformations) on gd 13.…”
Section: Endpoints Affected By Restraint: External Malformationmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition to standard tube, taping, and wire mesh restraints, confinement in an apparatus used to deliver radiation dosing to pregnant mice has been studied (Michel and Fritz‐Niggli, 1978). Following up on previous observations made during radiation experiments, the investigators used durations of 1.8, 10, 20, and 36 min on gd 8 and looked at abnormal fetuses (intrauterine growth retardation and external malformations) on gd 13.…”
Section: Endpoints Affected By Restraint: External Malformationmentioning
confidence: 99%
“…However, the details of this early experiment were not well described. The shortest effective restraint periods reported were <40 min (Michel and Fritz‐Niggli, 1978). The restraint method in the experiment was unique, a radiation exposure chamber described as allowing “no free movements.” Another difference from more standard restraint experiments was an examination of the fetuses on gd 13 rather than at term.…”
Section: Endpoints Affected By Restraint: Effects Produced Organogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that maternal stress causes growth retardation, cleft palate or resorption of fetuses in rodents [3,20,32]. Increased production of glucocorticoids during maternal stress mediating embryo-fetal toxicities including cleft palate and skeletal malformations has been proposed as a possible mechanism [4][5][6]21], and has been demonstrated that excess exposure to glucocorticoids retards fetal growth in animals and humans [22,25,30,34].…”
Section: Introductionmentioning
confidence: 99%